Human naive epiblast cells possess unrestricted lineage potential - Guo, Ge (Cell Stem Cell, 2021)
Classic embryological experiments have established that the early mouse embryo develops via sequential lineage bifurcations. The first segregated lineage is the trophectoderm, essential for blastocyst formation. Mouse naive epiblast and derivative embryonic stem cells are restricted accordingly from producing trophectoderm. Here we show, in contrast, that human naive embryonic stem cells readily make blastocyst trophectoderm and descendant trophoblast cell types. Trophectoderm was induced rapidly and efficiently by inhibition of ERK/mitogen-activated protein kinase (MAPK) and Nodal signaling. Transcriptome comparison with the human embryo substantiated direct formation of trophectoderm with subsequent differentiation into syncytiotrophoblast, cytotrophoblast, and downstream trophoblast stem cells. During pluripotency progression lineage potential switches from trophectoderm to amnion. Live-cell tracking revealed that epiblast cells in the human blastocyst are also able to produce trophectoderm. Thus, the paradigm of developmental specification coupled to lineage restriction does not apply to humans. Instead, epiblast plasticity and the potential for blastocyst regeneration are retained until implantation.